2008
DOI: 10.1111/j.1745-4603.2008.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crystalline Milk Fat on Rheological Properties of Ice Cream Mix Emulsions During Aging Time at 4c

Abstract: The influence of aging time at 4C has been studied for three ice cream mix emulsions containing 10% weight fraction of milk fat samples differing by their composition. Milk fat composition was varied by partially replacing anhydrous milk fat (AMF) either by a high melting temperature, stearin (AMF/S), or a low melting temperature, oleain (AMF/O) fraction. Among the three ice cream mix emulsions, the AMF/O emulsion containing the lowest proportion of saturated triglycerides had slightly lower proportion of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(64 reference statements)
0
7
0
5
Order By: Relevance
“…Bazmi, Launay, Cuvelier, and Relkin (2008) showed that the shear-stability and structure recovery of ice cream emulsions is related to the rate of development of fat crystals in the milk fat droplets, which in turn is dependent on milk fat composition; replacing a part of the anhydrous milk fat with high-melting fractions made the initial gel network more stable to shearing. However, during 24 h storage at 4 C, the solid fat content increased and the degree of structural recovery decreased in the emulsion with high-melting milk fat fraction, while these characteristics remained unchanged in the emulsion with low-melting milk fat fraction (Bazmi et al, 2008). On the other hand, during quiescent freezing, the ice cream emulsion formulated with low-melting milk fat fraction was less stable and much more susceptible to fat droplet aggregation-coalescence than the emulsions formulated with high-melting milk fat fraction or intact milk fat (Bazmi & Relkin, 2006).…”
Section: Applications Of Milk Fat Fractionsmentioning
confidence: 98%
“…Bazmi, Launay, Cuvelier, and Relkin (2008) showed that the shear-stability and structure recovery of ice cream emulsions is related to the rate of development of fat crystals in the milk fat droplets, which in turn is dependent on milk fat composition; replacing a part of the anhydrous milk fat with high-melting fractions made the initial gel network more stable to shearing. However, during 24 h storage at 4 C, the solid fat content increased and the degree of structural recovery decreased in the emulsion with high-melting milk fat fraction, while these characteristics remained unchanged in the emulsion with low-melting milk fat fraction (Bazmi et al, 2008). On the other hand, during quiescent freezing, the ice cream emulsion formulated with low-melting milk fat fraction was less stable and much more susceptible to fat droplet aggregation-coalescence than the emulsions formulated with high-melting milk fat fraction or intact milk fat (Bazmi & Relkin, 2006).…”
Section: Applications Of Milk Fat Fractionsmentioning
confidence: 98%
“…At 5/5 MPa, the D 4,3 measured 1.02 (± 0.15) μm, while a D 4,3 of 0.58 (± 0.02) and 0.52 (± 0.03) μm could be observed at 13/5 and 20/5 MPa, respectively. Also Bazmi et al [4] could not detect a significant influence of ageing on particle size, even though they observed slightly smaller particles in ice cream mix prepared from milk fat enriched with an olein fraction compared to a control milk fat and milk fat enriched with a stearin fraction. In addition, Koxholt et al [17] reported an inverse relationship between homogenization pressure and particle size, which was similar to our findings and followed the homogenization theory.…”
Section: Physicochemical Characterization Of Ice Cream MIXmentioning
confidence: 99%
“…This phenomenon requires the presence of a proportion of solid fat in the dispersed lipid phase, as fat globules are joined when a solid fat crystal from one globule penetrates into the liquid oil portion of another globule [5][6][7]. Thus, the degree of partial coalescence is highly dependant on the solid fat content [6,8]. Other authors were able to imitate this behavior by developing model cream-like emulsions prepared with milk protein and vegetable fat [9].…”
Section: Introductionmentioning
confidence: 99%